PEMBERDAYAAN GENERASI MUDA MAHASISWA DALAM PENGENALAN PRODUK LOKAL MASYARAKAT TERINTEGRASI PEMBELAJARAN KAMPUS: PEMBERDAYAAN GENERASI MUDA MAHASISWA DALAM PENGENALAN PRODUK LOKAL MASYARAKAT TERINTEGRASI PEMBELAJARAN KAMPUS - Ade Ismail; Fajar Maulana Wijaya Kusumah; Ika Yuliasari (PT. RANESS MEDIA RANCAGE, 2024)
Creativity and Entrepreneurship course as a course that includes a useful project as an actualization of Pancasila and Jatidiri values in an innovative and creative way. OKK students created the 'Villana' project which is taken from the words Village and Jatinangor.